PENDIDIKAN KESEHATAN TENTANG RESIKO TINGGIKEHAMILAN PADA IBU HAMIL DAN IBU YANG MEMILIKI BALITA DI PUSKESMAS DESA BINJAI KECAMATAN MEDAN DENAI SUMATERA UTARA - Lubis, Anita Damayanti; Rangkuti, Saddiyah; Nila Hayati; Niasty Lasmy Zaen; Muslima Pase; Harahap, Nurhayani; Tifani Hadi Tri Wahyuni (Jurnal Pengabdian Masyarakat Sapangambei Manoktok Hitei, 2024)
High-risk pregnancy is a condition that has the potential to cause illness or death for both the pregnant mother and the baby before delivery. The characteristics of high-risk pregnant women include being over the age of 35, which is considered unsafe because the reproductive organs begin to decline in function at that age. Other risk factors include a height of less than 145 cm, a weight of less than 45 kg, a pregnancy spacing of less than 2 years from the previous child, and having more than 4 children. The goal of this community service activity is to increase mothers' knowledge about high-risk pregnancy in hopes of reducing maternal and child mortality rates. The educational activity was conducted with 5 respondents, consisting of 1 pregnant woman and 4 mothers with toddlers, through health education delivered using leaflets as a health promotion tool. This activity involved planning, implementation, evaluation, and reporting stages. The results showed that all participants were able to understand the material presented. The respondents gave positive feedback, enthusiastically asking questions and sharing the information on social media. In conclusion, education about high-risk pregnancy needs to be conducted repeatedly and in an engaging manner to be effective. Collaboration between healthcare professionals and parents, especially pregnant women and mothers with toddlers, is crucial in efforts to increase public knowledge.   Keywords: High-risk pregnancy, pregnant women, mothers with toddlers, health education.